No Further Action: Contextualising Social Care Decisions for Children Victimised in Extra-Familial Settings. (April 2020) - Lloyd, Jenny; Firmin, Carlene
England's child protection system is intended to safeguard young people at risk of significant harm – physical, sexual, emotional abuse and neglect. When young people are physically assaulted, stabbed or groomed into drugs trafficking they experience significant harm. To this extent they are entitled to support from statutory child protection services. Using findings from one component of a mixed method multi-site study, data from referrals and assessments into children's social care is examined to identify the extent to which the right support and protection is realised. Such analysis indicates that despite being at risk of significant harm, young people abused in community or peer, rather than familial, settings will most likely receive a 'no further action' decision from social workers following referrals for support. This article suggests that to a certain extent no further action decisions are aligned to the legal and cultural parameters of social work and child protection practice, thus raising questions about the sufficiency of such for safeguarding young people abused in extra-familial settings.